Retinal ganglion cell dysfunction is correlated with disturbed visual cognition in schizophrenia patients with visual hallucinations. (April 2021) - Bernardin, Florent; Schwitzer, Thomas; Angioi-Duprez, Karine; Giersch, Anne; Ligier, Fabienne; Bourion-Bedes, Stéphanie; Jansen, Claire; Schwan, Raymund; Laprevote, Vincent
Highlights: Schizophrenia patients have visual cognition deficits and retinal dysfunctions. Visual cognition is lower in patients with visual hallucinations (VH). Retinal functions are associated with lower visual cognition in patients with VH. Abstract: Patients with schizophrenia have altered visual cognition and retinal functions. No studies have explored if retinal anomalies are related to visual cognition and the presence of visual hallucinations (VH). We explored functional responses of the retinal ganglion cells in schizophrenia patients with or without VH and conducted a neuropsychological evaluation to explore the links between cognition and retinal function. The VH+ group showed poorer visual cognition and we found correlations between the amplitudes of the P50 and the N95 waves and visual cognition. Our results provide arguments for a link between retinal dysfunction, impaired visual processing and VH in schizophrenia.